Substrate Entrainment, Depositional Relief, and Sediment Capture: Impact of a Submarine Landslide on Flow Process and Sediment Supply - Martínez-Doñate, A.; Privat, A. M-L. J.; Hodgson, D. M.; Jackson, C. A-L.; Kane, I. A.; Spychala, Y. T.; Duller, R. A.; Stevenson, C.; Keavney, E.; Schwarz, E.; Flint, S. S. (Frontiers in Earth Science, 2021)
Submarine landslides can generate complicated patterns of seafloor relief that influence subsequent flow behaviour and sediment dispersal patterns. In subsurface studies, the term mass transport deposits (MTDs) is commonly used and covers a range of processes and resultant deposits. While the large-scale morphology of submarine landslide deposits can be resolved in seismic data, the nature of their upper surface and its impact on both facies distributions and stratal architecture of overlying deposits is rarely resolvable. However, field-based studies often allow a more detailed characterisation of the deposit. The early post-rift Middle Jurassic deep-water succession of the Los Molles Formation is exceptionally well-exposed along dip-orientated WSW-ENE outcrop belt in the Chacay Melehue depocentre, Neuquén Basin, Argentina. We correlate 27 sedimentary logs constrained by marker beds to document the sedimentology and architecture of a >47m thick and >9.6km long debrite, which comprises two different types of megaclasts. The debrite overlies ramps and steps, indicating erosion and substrate entrainment. Two distinct sandstone-dominated units overlie the debrite. The lower sandstone unit is characterised by: i) abrupt thickness changes, wedging and progressive rotation of laminae in sandstone beds associated with growth strata; and ii) detached sandstone load balls within the underlying debrite. The combination of these features suggests syn-sedimentary foundering processes due to density instabilities at the top of the fluid-saturated mud-rich debrite. The debrite relief controlled the spatial distribution of foundered sandstones. The upper sandstone unit is characterised by thin-bedded deposits, locally overlain by medium- to thick-bedded lobe axis/off-axis deposits. The thin-beds show local thinning and onlapping onto the debrite, where it develops its highest relief. Facies distributions and stacking patterns record the progradation of submarine lobes and their complex interaction with long-lived debrite-related topography. The emplacement of a kilometre-scale debrite in an otherwise mud-rich basinal setting and accumulation of overlying sand-rich deposits suggests a genetic link between the mass-wasting event and transient coarse clastic sediment supply to an otherwise sand-starved part of the basin. Therefore, submarine landslides demonstrably impact the routing and behaviour of subsequent sediment gravity flows, which must be considered when predicting facies distributions and palaeoenvironments above MTDs in subsurface datasets.